In Vivo Radionuclide Generators for Diagnostics and Therapy. (12th December 2016) - Edem, Patricia E.; Fonslet, Jesper; Kjær, Andreas; Herth, Matthias; Severin, Gregory
Abstract : In vivo radionuclide generators make complex combinations of physical and chemical properties available for medical diagnostics and therapy. Perhaps the best-known in vivo generator is 212 Pb/ 212 Bi, which takes advantage of the extended half-life of 212 Pb to execute a targeted delivery of the therapeutic short-lived α -emitter 212 Bi. Often, as in the case of 81 Rb/ 81 Kr, chemical changes resulting from the transmutation of the parent are relied upon for diagnostic value. In other instances such as with extended alpha decay chains, chemical changes may lead to unwanted consequences. This article reviews some common and not-so-common in vivo generators with the purpose of understanding their value in medicine and medical research. This is currently relevant in light of a recent push for alpha emitters in targeted therapies, which often come with extended decay chains.